Antinociceptive and Anti-Inflammatory Activities of Leaf Methanol Extract of Cotyledon orbiculata L. (Crassulaceae) - George J. Amabeoku; Joseph Kabatende (Hindawi Limited, 2012)
Leaf methanol extract of C. orbiculata L. was investigated for antinociceptive and anti-inflammatory activities using acetic acid writhing and hot-plate tests and carrageenan-induced oedema test in mice and rats, respectively. C. orbiculata (100-400 mg/kg, i.p.) significantly inhibited acetic acid-induced writhing and significantly delayed the reaction time of mice to the hot-plate-induced thermal stimulation. Paracetamol (300 mg/kg, i.p.) significantly inhibited the acetic acid-induced writhing in mice. Morphine (10 mg/kg, i.p.) significantly delayed the reaction time of mice to the thermal stimulation produced with hot plate. Leaf methanol extract of C. orbiculata (50-400 mg/kg, i.p.) significantly attenuated the carrageenan-induced rat paw oedema. Indomethacin (10 mg/kg, p.o.) also significantly attenuated the carrageenan-induced rat paw oedema. The LD50 value obtained for the plant species was greater than 4000 mg/kg (p.o.). The data obtained indicate that C. orbiculata has antinociceptive and anti-inflammatory activities, justifying the folklore use of the plant species by traditional medicine practitioners in the treatment of painful and inflammatory conditions. The relatively high LD50 obtained shows that C. orbiculata may be safe in or nontoxic to mice.